PENGARUH DAYA TARIK IKLAN, KREATIVITAS IKLAN DAN KREDIBILITAS ENDORSER TERHADAP EFEKTIVITAS IKLAN DAN SIKAP KONSUMEN PADA SABUN PEMUTIH WAJAH MEREK OIL OF OLAY DI KOTA PEKANBARU - Legasari, Vionita Eka; Indarti, Sri; Restuti, Sri (Jurnal Ekonomi, 2013)
This research was conducted to the viewers of television commercial of Oil ofOlay whitening facial soap. The goal is to determine the direct and indirect effectsof advertising attraction, advertsing creativity and endorser credibility on theattitudes of consumers through advertising effectiveness.The study population included the viewers of television commercials of Oil ofOlay whitening facial soap in Pekanbaru. Research sample consisted of 179viewers chosen by purposive sampling technique. Independent variables were theattraction advertising research, advertising creativity and endorser credibility;while the attitude of of consumers was the dependent variable and theeffectiveness of advertising was the intervening variable. The data were analyzedby a path analysis using SPSS 17 for Windows.The results show that advertising attraction, advertising creativity and endorsercredibility both simulaneously and partially has a positive and significant effecton the advertising effectiveness and the attitude of the consumers. Partially, theadvertising effectiveness has a positve and significant effect on the attitude ofconsumers. Endorser credibility was the most dominant factor to affect theadvertising effectiveness and the attitude of the consuers. It is then recommendedthat the advertising setting be based on the cultural concepts and local values tomake it different from the same advertising themes of the same product. It is alsorecommended to choose female endorsers with the Indonesian characters and skinfaces.Kata Kunci: Advertising Attraction, Advertising Creatvity, EndorserCredibility, Advertisingeffectiveness and The Attitude ofConsumers.